Practical power distribution for industry. - De Kock, Jan (Practical professional books from Elsevier.)
The book provides technical know-how not covered by most universities and colleges in a subject that is central to the roles of many electrical engineers in industry, focusing on switchgear, power cables, power factor correction, and network studies. *Learn how to install and maintain electrical power equipment in industrial settings*Select and specify the right power system at the right price*Provides the practical essentials for reliable operation of industrial electrical networks - covering switchgear, cabling and power correction factors.